2019
DOI: 10.1002/app.47870
|View full text |Cite
|
Sign up to set email alerts
|

Photo‐responsive block copolymer containing azobenzene group: Synthesis by reversible addition‐fragmentation chain transfer polymerization and characterization

Abstract: The design and synthesis of a new azobenzene‐based methacrylate monomer (Azo‐IEM) was demonstrated, and its polymerization behavior during reversible addition‐fragmentation chain transfer (RAFT) polymerization was investigated. Well‐defined homopolymer and amphiphilic block copolymer containing Azo‐IEM monomeric units were successfully prepared as evidenced by NMR and GPC analysis. Moreover, the photo‐triggered reversible isomerization of polymer products in selected solvents was investigated. Finally, TEM ana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 37 publications
0
4
0
Order By: Relevance
“…In addition, TEM analysis showed that the morphology of the nanoparticles of the block copolymer samples was significantly different under different light wavelengths. [28] Azobenzene polymers have high spatial and temporal resolution, photoinduced healing and processing properties due to the photoisomerization of some azobenzene polymers that can lead to solid-liquid reversible transformation shown in Figure 2d. The researchers investigated the synthesis and photoresponse of azobenzene polymers with different spacer lengths between the polymer backbone and side-chain azobenzene monomers.…”
Section: Photoswitchable Adhesives Based On Azobenzene-containing Pol...mentioning
confidence: 99%
“…In addition, TEM analysis showed that the morphology of the nanoparticles of the block copolymer samples was significantly different under different light wavelengths. [28] Azobenzene polymers have high spatial and temporal resolution, photoinduced healing and processing properties due to the photoisomerization of some azobenzene polymers that can lead to solid-liquid reversible transformation shown in Figure 2d. The researchers investigated the synthesis and photoresponse of azobenzene polymers with different spacer lengths between the polymer backbone and side-chain azobenzene monomers.…”
Section: Photoswitchable Adhesives Based On Azobenzene-containing Pol...mentioning
confidence: 99%
“…Given the unique properties of dual-responsive polymers, we attempt to design and synthesize a type of polymer in simultaneous response to the pH and light stimulations and explore their performance in broader applications related to reversible emulsi cation and adsorption. Light-sensitive polymers can change the hydrophobic-hydrophilic balance by photoreaction upon irradiating with light, which generally incorporates photochromic groups (i.e., azobenzenes, o-nitrobenzyl esters) into the side chains 1,22,23 . In particular, these polymers with azobenzene structures can guarantee the reversible cis-trans isomerization with respect to light irradication 24,25 .…”
Section: Introductionmentioning
confidence: 99%
“…The function of light control is often achieved by introducing light responsive groups into the system by methods like incorporation, [9] addition, [10] modification, [11] etc. Azobenzene derivatives are often used to achieve the purpose of photocontrolled debonding and reuse, whose physical and chemical properties are changed significantly by their photoisomerization under irradiation.…”
Section: Introductionmentioning
confidence: 99%